2011
DOI: 10.1007/s11739-011-0512-z
|View full text |Cite
|
Sign up to set email alerts
|

Aging reduces complexity of heart rate variability assessed by conditional entropy and symbolic analysis

Abstract: Increasing age is associated with a reduction in overall heart rate variability as well as changes in complexity of physiologic dynamics. The aim of this study was to verify if the alterations in autonomic modulation of heart rate caused by the aging process could be detected by Shannon entropy (SE), conditional entropy (CE) and symbolic analysis (SA). Complexity analysis was carried out in 44 healthy subjects divided into two groups: old (n = 23, 63 ± 3 years) and young group (n = 21, 23 ± 2). It was analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
11

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 28 publications
3
59
0
11
Order By: Relevance
“…These findings suggest that the magnitude of the HP changes became smaller and HP dynamics turned out to be more regular and predictable as a function of age. These results are in agreement with previous studies regardless of whether they are based on entropy rates [14,15,17,18,22,23,28,34] or on different metrics [2,13,15,16,19,22,23,29,34].…”
Section: Complexity Of the Hp Variability At Rest: Aging And Gender Esupporting
confidence: 93%
See 2 more Smart Citations
“…These findings suggest that the magnitude of the HP changes became smaller and HP dynamics turned out to be more regular and predictable as a function of age. These results are in agreement with previous studies regardless of whether they are based on entropy rates [14,15,17,18,22,23,28,34] or on different metrics [2,13,15,16,19,22,23,29,34].…”
Section: Complexity Of the Hp Variability At Rest: Aging And Gender Esupporting
confidence: 93%
“…These changes are mirrored by a reduction in heart period (HP) variability [2][3][4][5][6][7][8][9], by an increase of systolic blood pressure (SAP) variability [10][11][12], and by a reduction in complexity of physiological dynamics [2][3][4][13][14][15][16][17][18][19][20][21][22][23]. Although the abovementioned studies indicate that aging reduces the complexity of the cardiovascular control and prove the gender dependence, it is still unclear whether the complexity reduction and the gender relation are similarly observable from HP and SAP variabilities and if it persists during a cardiovascular control challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these standards are grouped according to the number and type of variations 23 . Studies with pharmacological blockers and autonomic tests have shown that the index with no variation (0V) and two unlike variations (2ULV) indicate sympathetic and parasympathetic modulation, respectively 24 . Unstable segments were avoided, since data stability is a prerequisite for symbolic analyses 25 .…”
Section: Analysis Of the Heart Rate Recovery And Heart Rate Variabilitymentioning
confidence: 99%
“…HRV changes with aging, [4] anesthesia [5][6][7] and exercise [8,9]. Indices of various nonlinear dynamic analyses such as approximate entropy (ApEn) or Hurst exponent (H) for HRV are useful for diagnosis or predictors of prognosis in some clinical situations [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%